Roles of arbuscular mycorrhizal fungi in plant growth and disease management for sustainable agriculture - Umer, Muhammad; Anwar, Naureen; Mubeen, Mustansar; Li, Yun; Ali, Amjad; Alshaharni, Mohammed O.; Liu, Pingwu (Frontiers in Microbiology, 2025)
Arbuscular mycorrhizal fungi (AMF) are the basis symbionts in terrestrial ecosystems, profoundly influencing plant development, nutrient acquisition, and resilience to biotic and abiotic stresses. This review synthesizes current systematic understandings of AMF-mediated augmentation of plant growth and disease resistance, with a particular emphasis on their role in sustainable crop production. AMF improves host plant performance through enhanced phosphorus, nitrogen, and water uptake via extensive extraradical hyphal networks. Moreover, AMF colonization modulates phytohormonal signaling pathways, including salicylic acid, jasmonic acid, abscisic acid, and nitric oxide, priming SR and upregulating defense-related gene expression. Increased biosynthesis of secondary metabolites, reinforcement of cell walls, and activation of antioxidant enzyme systems often accompany these responses. AMF also engage in synergistic interactions with rhizosphere microbiota such as Trichoderma, Pseudomonas, and Bacillus, enhancing their collective biocontrol efficacy against a broad spectrum of soil-borne pathogens, including fungi, bacteria, and nematodes. Through modulation of root exudates, glomalin-mediated soil aggregation, and microbiome restructuring, AMF contributes to the establishment of disease-suppressive soils. Genomic and transcriptomic studies have elucidated key components of the common symbiosis-signaling pathway, supporting AMF-host specificity and functional outcomes. AMF is a promising biotechnological tool for integrated pest, disease, and nutrient management. Advancing their application in field settings requires targeted research on strain-host-environment interactions, formulation technologies, and long-term ecosystem impacts, aligning AMF-based strategies with the goals of resilient and sustainable agriculture.